2020
DOI: 10.15766/mep_2374-8265.11047
|View full text |Cite
|
Sign up to set email alerts
|

Advanced Communication and Examination Skills in Telemedicine: A Structured Simulation-Based Course for Medical Students

Abstract: Introduction Telemedicine has become part of mainstream medical practice. High quality virtual care is a skill that will be required of many physicians. Skills required for effective evaluation and communication during a video encounter differ from skills required at bedside, yet few rubrics for educational content and student performance evaluation in telemedicine training have been developed. Our objective was to develop, implement, and assess a training module designed to teach medical provider… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
55
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(58 citation statements)
references
References 17 publications
1
55
0
2
Order By: Relevance
“…145 To overcome these limitations, a new curriculum is being developed to train providers in "web-side manner." 147 In general, telemedicine does not facilitate high-quality communication between patients and providers. Nonverbal cues can be missed, including facial expressions hidden by masks.…”
Section: Reassignment Of Precharting and Data Entry Tasks To Medical Assistantsmentioning
confidence: 99%
“…145 To overcome these limitations, a new curriculum is being developed to train providers in "web-side manner." 147 In general, telemedicine does not facilitate high-quality communication between patients and providers. Nonverbal cues can be missed, including facial expressions hidden by masks.…”
Section: Reassignment Of Precharting and Data Entry Tasks To Medical Assistantsmentioning
confidence: 99%
“…The need to adapt communication skills for telemedicine has been increasingly recognized, prompting the development of training modules to educate medical students in building rapport and trust through video visits. [ 8 ] Early literature shows that many patients report equal or greater satisfaction with physicians’ communication in telemedicine compared with in-person visits. [ 9 , 10 ] One review found that 19 out of 21 included studies positively rated the efficacy of communication via virtual care.…”
Section: Discussionmentioning
confidence: 99%
“…Case-based discussions and pre-clinic team huddles can help to highlight high-risk patient safety concerns and teach ways to triage patients for in-person or emergency care. 14 , 28 , 31 , 32 Faculty should direct learners to survey the patient environment for safety, identify cases for interdisciplinary collaborative care, and contextualize patient characteristics and disease presentations during virtual care encounters. 32 Similarly, learners may encounter patients with sensitive issues or limited ability to engage in virtual visits.…”
Section: Integration Of Aamc Telehealth Competencies and Acgme Milest...mentioning
confidence: 99%